SPECIAL ASPECTS OF IMPLANTATION OF A HEART PUMP SUPPORT SYSTEM AVK-N AS A «BRIDGE» TO HEART TRANSPLANTATION - T. A. Khalilulin; V. M. Zacharevich; V. N. Poptsov; G. P. Itkin; A. O. Shevchenko; R. Sh. Saitgareev; A. M. Goltz; A. R. Zakiryanov; N. N. Koloskova; N. N. Abramova; N. Y. Zacharevich; E. A. Nikitina; et al. (Вестник трансплантологии и искусственных органов, 2018)
Aim: to develop an optimal surgical tactic for implantation of “AVK-N” system as a “bridge” to heart transplantation.Materials and methods. 17 patients were included. They were operated in the period from 2012 to October 2017 in Federal State Budgetary Institution «V.I. Shumakov National Medical Research Center of Transplantology and Artifi cial Organs». A tiny implantable system «Portable device for assisting cardiac circulation» (AVK-N; Russia) was used for replacing the pumping function of the left ventricle. All patients were examined according to the program of potential recipients for heart transplantation, before the applying of prolonged mechanical circulatory support. Among the operated patients there were 16 (94.1%) men and 1 (5.9%) woman, the average age was 52.64 ± 10.56 (from 33 to 67 years). All patients had congestive heart failure III–IV functional class according to NYHA, refractory to optimal drug therapy. Heart failure was triggered by dilated cardiomyopathy in 12 (70,58%) cases, and by postinfarction systolic dysfunction of the left ventricle in 5 (29,42%). Implantation of «AVK-N» system was performed to potential recipients of the donor heart with terminal stage of CHF with a decrease in LV ejection fraction up to 10%.Results. As a result of this study there were developed several technological aspects facilitating the subsequent heart transplantation.Conclusion. Our experience in optimizing the surgical tactics of the “AVK-N” system implantation as a bridge to heart transplantation, demonstrated the possibility and safety of its active use in both patients with terminal heart failure on the waiting list of heart transplantation and patients having temporary contraindications to HTX.